Unraveling the pathogenomics of Rhizoctonia solani infecting proso millet (Panicum miliaceum L.): genomic perspective on ruthless virulence and adaptive evolution - Koti, Prasanna S.; Patro, T. S. S. K.; Palanna, K. B.; Jeevan, B.; Prasanth, Porapu; Ramesh, G. V.; Anuradha, N.; Rani, Y. Sandhya; Triveni, Ungata; Devi, K. Lavanya; Poonacha, T. Tharana; Khan, Farooq; et al. (Frontiers in Microbiology, 2025)
IntroductionBanded sheath blight (Bsb), caused by Rhizoctonia solani, is an emerging threat to proso millet cultivation, significantly impacting yield and grain quality. This study on the pathogenomics of R. solani seeks to unravel its genetic mechanisms, identify key virulence factors, decode host-pathogen interactions, and pinpoint molecular targets for effective control strategies.MethodsR. solani isolates were collected from various regions across India, resulting in six distinct isolates. These isolates were comprehensively characterized through morphological observations, molecular analyses, and virulence assessments to gain comprehensive insights into their diversity and pathogenic potential. The most virulent strain, designated VAP-1, infecting proso millet, was sequenced using the Illumina platform and de novo assembled using the SPAdes assembler, resulting in a highly complete genome. Functional regions of the genome were predicted and annotated using Funannotate. A subsequent comparative genomics study and secretome analysis were conducted to support functional genomic investigations.ResultsThe VAP-1 genome assembly resulted in a total size of 47.12 Mb, with approximately 17.62% of the genome consisting of repetitive sequences, predominantly dominated by interspersed elements (around 97.8%). These interspersed elements were primarily classified as retrotransposons (72%), with DNA transposons comprising a smaller proportion (5%), while the remaining interspersed sequences were not fully annotated. Functional analysis of the genome revealed significant enrichment in KEGG pathways, including “Carbohydrate metabolism,” “Translation,” “Signal transduction,” and “Transport and catabolism.” In addition, Gene Ontology (GO) terms such as “Proteolysis,” “Membrane,” and “ATP binding” were notably enriched. The secretory protein profile of the VAP-1 genome from R. solani features key proteins from the major facilitator superfamily (MFS) transporters, (Trans) glycosidases, P-loop containing nucleoside triphosphate hydrolases, and galactose oxidase, all within the central domain superfamily. Glycoside hydrolases represent the largest class of CAZymes in the VAP-1 genome. Comparative genomic analysis of VAP-1 with other R. solani strains infecting Poaceae (e.g., rice) and non-Poaceae (e.g., sugar beet and tobacco) hosts showed that VAP-1 clusters closely with rice-infecting strains at the species level, yet exhibits a greater divergence in genomic similarity from strains infecting sugar beet and tobacco. Notably, variations were observed in important secretory proteins, such as multiple base deletions in MFS proteins across strains infecting proso millet, rice, and sugar beet.DiscussionFunctional analysis of the VAP-1 genome has unveiled a wealth of insights, though we have only begun to scratch the surface. KEGG and GO annotations point to critical proteins that are essential for host infection, providing the pathogen with a potent arsenal for successful penetration, survival, and dissemination within the host. The secretory proteins encoded in the VAP-1 genome play a pivotal role in equipping the pathogen with the necessary tools to degrade plant cell wall polymers, release cell wall-bound saccharides, and break down polysaccharides for energy utilization and host colonization. Notable variations were observed in several secretome superfamily proteins within the VAP-1 strain. These findings underscore the genomic diversity present within R. solani strains and suggest possible adaptations that may contribute to host specificity.